Multiple Class Membership Verbs: (A syntactic –Semantic Study) - Imad Hussein Ahmed; Adday Mahmood Adday (PROSPECTIVE RESEARCHES, 2023)
This research deals with some of the verbs that give certain meanings, when they followed by a certain complementation of the verb. This means that verb complementation restricts the verb uses and meanings in certain verbs. Many examples given to shed the light on these verbs mentioned earlier. The different meanings of verbs are affected by the complementation that follows them and the way that complementation can affect the original meaning of the verb itself semantically and syntactically. The items that follow these verbs, are obligatory and not optional, complete the verb meaning. The complementation restricts the syntactic and semantic analysis of the verb. In addition, other functions affect the original meaning of the verb like metaphor, syntactic structure, intonation, the intended meaning of the speaker and other certain situations. These items can change the syntactic and semantic features of verbs.